Electronic readout characterisation of a new soft X-ray diagnostic for burning plasma. (1st August 2022) - Cancelli, S.; Muraro, A.; Perelli Cippo, E.; Abba, A.; Corradi, G.; Grosso, G.; Gorini, G.; Kushoro, M.H.; Murtas, F.; Putignano, O.; Scionti, J.; Tagnani, D.; et al.
Abstract: In fusion plasma scenario, soft X-rays are important tools to study impurities inside plasma. However state-of-the-art silicon detectors cannot survive for long time to the heavy damages due to harsh conditions in tokamaks. GEM detectors are a good alternative thanks to their resilience to radiation damage. In this paper, a GEM detector coupled with new dedicated electronic readout based on GEMINI chip is described. In particular, the detector response has been studied comparing the well established PH method and the ToT method implemented in GEMINI. The results indicate the possibility of using this electronic readout to do soft X-ray spectroscopy measurements in the energy range up to about 10–20 keV.